Rancang Bangun Sistem Informasi Pemesanan Custom Furniture pada CV. Adidewata Berbasis Website - Putra, Mochammad Adi Priyono; Putra, I Gede Juliana Eka; Anggara, I Nyoman Yudi (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Custom furniture product ordering and sales handling that is still operated manually that makes customers have to come to the company for every custom furniture ordering, where the accumulation of data resulting in loss. Custom furniture ordering information systems are designed to promote sales strategies and enhance online product ordering which facilitates the company and customers in ordering and selling purchases. The method used to design this research system is Rapid Application Development (RAD) which is the process of business modelling, data modelling and process modeling, modeling implementation, application building, and testing. Website-based custom furniture ordering information system design using HTML, CSS, PHP, and MySQL database programming languages, the purpose of the creation of this information system to facilitate customers who no longer have to come to the company to order, buy, view product information, as well as facilitate payment, and ordering and selling product data is organized in the system.